Untreated wastewater as a source of carbapenem-resistant bacteria to the riverine ecosystem - Hrenovic, Jasna; Durn, Goran; Kazazic, Snjezana; Dekic, Svjetlana; Music, Martina Seruga (Water SA, 2019)
Bacteriological pollution, especially that including clinically important bacteria, of the aquatic environment caused by anthropogenic pressure attracts much attention with regard to public health. Reports to date have not addressed the concentration of emerging carbapenem-resistant bacteria (CRB) in riverine ecosystems, and the source of this pollution is hard to track. We examined the impact of discharge of untreated wastewaters on the bacterial population in the riverine ecosystem, with emphasis on clinically important CRB using a small river in Croatia as a model. River sediments were analysed mineralogically and geochemically. Cultivation of CRB was performed at 37 and 42°C to distinguish the presumably environmental intrinsically resistant (CRB37) from the presumably clinically important acquired resistance (CRB42) species. The significantly positive correlation of CRB42 with CRB37 and total heterotrophs, but not with intestinal enterococci, suggests that entry of CRB42 in riverine ecosystem is not necessarily connected to faecal pollution. The numbers and prevalence of CRB42 are rather dependent on the type of pollution, and is connected to the discharge of wastewaters from different human and animal healthcare centres. Emerging hospital pathogens Acinetobacter baumannii and Klebsiella pneumoniae were exclusively isolated among CRB42 from river water after the discharge of wastewater of a general hospital. The CRB42, once discharged into the riverine ecosystem, behaves as part of the indigenous bacterial population, and could be spread through the natural water bodies or accumulate in river sediments. This implies the need for disinfection of hospital wastewater prior to its discharge into the natural environment in order to avoid the consequent public-health threat. The anthropogenic impact evidenced as bacteriological changes is accompanied by an increase in heavy metal concentrations in river sediments.